Dynamics and consequences of daily work-events: affective processes explain it - Junça Silva, A.; Caetano, António; Lopes, M. (IWP Conference 2016: Work and Organizational Psychology: Making a Difference, 2016)
In this study we aim to explore whether daily hassles and uplifts at work and work engagement can be considered as daily antecedents of well-being. We also intend to test if work engagement plays a mediating role in the relationship between daily hassles and uplifts and well-being on the daily level. To achieve this, we conducted two diary studies. Instudy 1, we explored this relationship on a sample of one hundred and eighty one part-time workers who answered a daily questionnaire for (at least) four days (N =181 × 4 = 724). The results of hierarchical linear modelling demonstrated that work engagement fully mediated the effects of daily uplifts on well-being and partially mediated the effects of daily hassles on well-being. In study 2, we extended the hypothesis to a sample of full-time employees. Fifty-one workers filled in a questionnaire at the end of each working day for ten consecutive days (N = 51 ×10 = 510). The results revealed that daily uplifts were positively associated with well-being. The effects of daily uplifts and hassles on well-being were fully mediated by work engagement. The relationships explored provide new theoretical elements for models that explain which variables influence employees’ well-being. The implications for employee health and organizational success are discussed.